Tambaqui (Colossoma macropomum) fish burger: optimization process and evaluation of oxidative stability - Presenza, Leandro da Silva (2022)
Fish are one of the main sources of protein in the human diet, and it has shown production rates in recent decades, mainly due to consumer interest in the intake of micro and macronutrients that have positive effects on the cardiovascular, cognitive and immune systems. In addition, fish stand out as a food security alternative for the next generations based on more sustainable production systems. However, studies point to the need for measures to boost the production and consumption of native species to achieve fish consumption targets. In this context, tambaqui (Colossoma macropomum) stands out as the Brazilian native species with the highest volume of production, and despite regionalized marketing, strategies aimed at inserting products of this species in retail can contribute to the development of more sustainable systems with the consumption of local products. In this study, a replicable optimization model was used as a strategy to develop a fish burger formulation based on mechanically separated meat (MSM) from tambaqui, focusing on cost reduction and improvements in physicochemical and sensory properties. The addition of the flour mixture showed a synergistic and significant effect to reduce costs and improve textural and sensory qualities, and the cooking yield was 12% higher than that of the formulation without flour (p < 0.05). Considering that fish are highly susceptible to deterioration, conventional fish-based products tend to have a short shelf life when no preservative agent is applied; in this sense, the second stage of the study was carried out to establish a clean label product. The addition of plant based bioactive compounds has been investigated as a potential agent to extend the shelf life of fish products. Extracts obtained from byproducts of avocado (Persea Americana Mill.) processing were added to the optimized fish burger formulation, and the biochemical and physicochemical properties were evaluated during storage at 4°C for 14 days and at -18° C for 90 days. The addition of extracts significantly prolonged the shelf life of the fish burgers. Although the treatment with sodium erythorbate was more efficient for the inhibition of lipid oxidation products (TBARS), the natural extracts showed a reduction in the development of peroxidation products and the formation of volatile nitrogenous bases (TVB-N), influencing the maintenance of freshness, lipid profile and proximate composition of fish burgers in both storage treatments (p < 0.05). In general, the results indicated that the use of byproducts from the food industry in line with applied statistical models can favor the development of new products with aspects of sustainability and healthiness.